The power of good people : surviving Sri Lanka's civil war - Para, Paheer; Corke, Alison (Wild Dingo Press, 2017)
Para was barely five years old when civil war erupted in Sri Lanka. Nearly three decades later it ended in appalling horror and bloodshed. Tens of thousands of innocent civilians died. Survival required courage, ingenuity -- and the kindness of strangers. This is Para's story of survival against all odds. In May 2009, Sri Lanka's long and dreadful civil war was finally brought to an horrific end. Ruthlessly driven to a small strip of land on the tip of the island's north-east coast, tens of thousands of innocent civilians died, smashed by artillery, killed by snipers, denied medical treatment, and starved to death beneath the baking sun. This ferocious battle consolidated and highlighted the terrors of the preceding twenty-six years of war, characterised by vicious murders and desperate acts from both sides, where civilians were bombarded, kidnapped, raped, and tortured with impunity. In such a vicious war, was there any room for humanity? Para Paheer's story could be one of tens of thousands, except that he lived to tell the world of the horrors; but more importantly, to record and pay tribute to those courageous people without whom he would probably not be alive. I know that I would not have survived without help from many people. Many put themselves in danger and at least one person died for me. It's time for me to remember them, and to thank them ... all the good people who helped me through those terrifying times when life was hard, and survival often only a matter of chance. While in Christmas Island Detention Centre, Para became penfriends with Alison Corke, a member of the Apollo Bay branch of Rural Australians for Refugees, in Victoria. On his release from detention in 2011, Para moved in with the Corke family. "From our first letters, exchanged while Para was in detention and trying to improve his English, I knew he was an exceptional young man, with an astonishing tale to tell. I am proud to be helping him share his story and to find and thank those people who helped him survive, often against massive odds ... Time and again, Para and I agreed that it is the little things that matter most -- those small, often unremembered acts of kindness that can change someone's world. We all have the power to do something; only we can choose whether to use that power for the good."
Keywords: Pararasasingam, Paheertharan, -- 1978-; Civil war -- Sri Lanka.; War victims -- Sri Lanka.; Refugees -- Sri Lanka -- Personal narratives.; Sri Lanka -- History -- Civil War, 1983-2009 -- Personal narratives.; Guerre civile -- Sri Lanka.; Victimes de guerre -- Sri Lanka.; Réfugiés -- Sri-Lanka -- Récits personnels.; Sri Lanka -- Histoire -- 1983-2009 (Guerre civile) -- Récits personnels.; HISTORY -- Asia -- India & South Asia.; Civil war; Refugees; War victims; Sri Lanka; 1983-2009; Australian; History; Personal narratives